Antifungal susceptibility pattern of Candida isolated from cutaneous candidiasis patients in eastern Guangdong region: A retrospective study of the past 10 years - Bilal, Hazrat; Hou, Bing; Shafiq, Muhammad; Chen, Xinyu; Shahid, Muhammad Akbar; Zeng, Yuebin (Frontiers in Microbiology, 2022)
Cutaneous candidiasis is one of the most prevalent mycotic infections caused by Candida species. The severity of infection mounts faster when the species shows antifungal resistance. In the current retrospective study, we aimed to analyze the occurrence, causes of cutaneous candidiasis, and antifungal susceptibility pattern of Candida isolates from Skin and Venereal Diseases Prevention and Control Hospital of Shantou, located in eastern Guangdong, China. The laboratory data of all patients (n =3113) of suffering from various skin and venereal infections during January 2012 to December 2021 was analyzed through Excel and GraphPad prism. Our analysis indicate that cutaneous candidiasis was 22.29% (n= 694), of which 78.53% (n=554) of patients were males and 21.47% (n=149) of patients were females. The median age of patients with cutaneous candidiasis was 38-year (interquartile range (30-48)). Most cases occurred in the adult age group (19-50 years). Regarding the species type, the C. albicans were prominently detected (n=664, 95.68%), while non-C. albicans were found only in 30 (4.32%) patients, which were C. glabrata (n= 18), C. krusei (n=8), C. tropicalis (n=3), and C. parapsilosis (n=1). The C. albicans susceptibility rate for terbinafine, miconazole, voriconazole, itraconazole, fluconazole, ketoconazole, nystatin, 5-flucytosine and amphotericin B were 10.83%, 29.32%, 59.39%, 78.53%, 85.28%, 87.75%, 99.59%, 99.41%, and 100% respectively. Finally, all isolates of C. glabrata were found susceptible to all tested azole drugs with exception to miconazole against which 8.33% of isolates showed resistance. The findings of this study will help healthcare officials to establish better antifungal stewardship in the region.